(untitled) (International Journal of Irrigation and Water Management, 2019)
In order to study effects of treated wastewater, with complete fertilizer sprayed on some forage quantitative and qualitative characteristics of foxtail millet (SETARIA ITALICA), A split plot experiment based on randomized complete block design (R.C.B design) with three replicates was carried out at the Agriculture Institute of Zabol University in south east Iran during 2009 growing season. Treatments included three levels of irrigation namely, irrigation with tap water at all stages of grows (control), irrigation with wastewater and tap water alternately, irrigation with wastewater for all growing stages, as the main plot and sprayed with three levels of complete fertilizer (NATBA-LIB): non-spraying (control), Sprayed with 600 g of complete fertilizer in each hectare, sprayed with 1200 g of complete fertilizer in each hectare, as were the subplots. According to the results, the irrigation with wastewater and complete fertilizer sprayed had a significant effect on yield and forage quality characteristics. Among the irrigation treatments, irrigation with wastewater for all growing stages cause increase of grain yield and forage quality characteristics such as soluble carbohydrate, crude protein, ash, dry matter digestibility and significant decrease in cell wall, cell wall without hemi cellulose and lignin percentage. Also the highest grain yield and dry matter digestibility were obtained from 1200 g of fertilizer sprayed in comparison with sprayed with 600 g of complete fertilizer and control treatments. Therefore, in order to achieve the desired quantitative and qualitative characteristics of forage millet, using the treated wastewater and complete fertilizer has recommended.